ANALISIS KESESUAIAN MATERI KIMIA SMA PADA TOPIK HUKUM-HUKUM DASAR KIMIA DAN STOIKIOMETRI DENGAN KOMPETENSI INTI DAN KOMPETENSI DASAR KURIKULUM 2013 - Hayanni, Gusrilla (rc-institut, 2019)
This research is interesting to see the suitability of the High School Chemistry learning process, namely on the topic of Basic Chemical Law and Stoichiometry with the resolution of the 2013 Core Competency and Basic Competency Competency formulas. The method used in this study is library research with supported data search techniques. After the data is collected, the content analysis is carried out. The results of this study consisted of three components, namely: the completeness of the material obtained as much as 60% (3 = quite complete), the component of excess material obtained 60% (3 = quite extensive), and the material component obtained was 87% (5 = very deep). Based on these results, an average yield of 69% was obtained. This means that the suitability of the material on the topic of Basic Chemistry and Stoichiometry with Core Competencies and Basic Competencies is 69% with a category sufficient to fit the value 3. Based on these results, the Basic Chemical and Stoichiometry material can be listed in the High School Chemistry published by the Curriculum The Ministry of Education and Culture 2013 is in accordance with the formulation of the 2013 Core Competencies and Basic Competencies.